2018
DOI: 10.1111/jsr.12742
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements in idiopathic rapid eye movement sleep behaviour disorder: High antisaccade error rate reflects prefrontal cortex dysfunction

Abstract: Abnormalities of eye movements have been reported in patients with Parkinson's disease (PD). However, it is unclear if they occur in the prodromal stage of synucleinopathy represented by idiopathic rapid eye movement sleep behaviour disorder (iRBD). We thus aimed to study eye movements in subjects with iRBD and in de novo PD, to assess if their abnormalities may serve as a clinical biomarker of neurodegeneration. Fifty subjects with polysomnography-confirmed iRBD (46 male, age 40-79 years), 18 newly diagnosed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 31 publications
0
24
2
Order By: Relevance
“…1C ). The discrepancy between our findings and previously reported RBD patients 26 in respect to direction errors in the anti‐saccade task needs further detailed and long‐term investigations (further discussion in Supplementary Materials S1 ). In line with previous PD studies, 22 , 25 , 28 both RBD and PD patients demonstrated significantly less pupil constriction during pro‐saccade trials (Fig.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…1C ). The discrepancy between our findings and previously reported RBD patients 26 in respect to direction errors in the anti‐saccade task needs further detailed and long‐term investigations (further discussion in Supplementary Materials S1 ). In line with previous PD studies, 22 , 25 , 28 both RBD and PD patients demonstrated significantly less pupil constriction during pro‐saccade trials (Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…Here, we explore whether RBD patients have comparable deficits in saccadic, pupil, and blink behavior during IPAST to PD patients (here, and previously reported) 22,24,25,[27][28][29] and reported RBD patients. 26 Differences between RBD and CTRL identify potential prodromal PD biomarkers in this cross-sectional study.…”
mentioning
confidence: 79%
“…CI confidence interval, HC healthy control group, PD group with Parkinson's disease, (m) mixed task design with prosaccades and antisaccades, SD standard deviation, Std. standardized ◂ (Briand et al, 1999), B14 (Bonnet et al, 2014b), B19 (Barbosa et al, 2019), C12 (Cameron et al, 2012), C00 (Crevits et al, 2000), E17 (Ewenczyk et al, 2017), G16 (Gorges et al, 2016), H10 (Harsay et al, 2010), H19 (Hanuška et al, 2019), L19 (Lu et al, 2019), L90 (Lueck et al, 1990), L16 (Lemos et al, 2016), M05 (Mosimann et al, 2005), N16 (Nemanich & Earhart, 2016), N19 (Nagai et al, 2019), R17 (Ranchet et al, 2017), RP15 (Rivaud-Péchoux et al, 2007), V19 (Visser et al, 2019), vK09 (van Koningsbruggen et al, 2009, W15 (Walton et al, 2015), W16 (Wang et al, 2016), W19 (Waldthaler et al, 2019a)…”
Section: Moderator Analysismentioning
confidence: 99%
“…While some studies demonstrated increased antisaccade error rates even in unmedicated patients in very early disease stages (Antoniades et al, 2015a;Hanuška et al 2019), others found no significant alterations of antisaccade latency or antisaccade error rate early and later in the disease course. (Ranchet et al, 2017;Nagai et al, 2019) As proposed by two recent studies (Lu et al, 2019;Waldthaler et al, 2019a), antisaccade latency might correlate with disease duration in PD without significant impact of dopaminergic medication.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies on eye movements in psychiatric and neurodegenerative diseases concluded that the dysfunction of cognitive and executive functions of the frontal lobe is easy to investigate by antisaccade error rate . In our recently published videooculographic study, we investigated prosaccades and antisaccades (movement to the opposite side that the target appears) in patients with idiopathic rapid eye movement sleep behavior disorder (RBD) and in subjects with untreated PD . PD patients in our study showed a hypometry ( P < 0.01) and trend toward a decrease in velocity compared with controls in prosaccades, which is in accordance with the study of Stuart et al We also found that antisaccade error rate is increased in both PD and RBD compared with healthy controls ( P < 0.05 and P < 0.01, respectively).…”
mentioning
confidence: 69%